2021
DOI: 10.1080/21655979.2021.2000229
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: LncRNA SOX2-OTinhibitionprotects against myocardialischemia/reperfusion-inducedinjury via themicroRNA-186-5p (miR-186-5p)/Yin Yang 1 (YY1)pathway

Abstract: Long noncoding RNAs (lncRNAs) exert essential effects in regulating myocardial ischemia/reperfusion (MI/R)-induced injury. This work intended to explore the functions of lncRNA SOX2-OT and its regulatory mechanism within MI/R-induced injury. In this study, gene expression was determined by RT-qPCR. Western blotting was applied for the detection of protein levels. Pro-inflammatory cytokine concentrations, cardiomyocyte viability, and apoptosis were detected via ELISA, CCK-8 and flow cytometry. In the in vitro m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Apart from this finding, we also discovered that high level serum exosomal miR-186-5p after PCI and its decrement percentage <median (35%) decrement was related to increased MACE in AMI patients. The potential arguments would be that: (1) exosomal miR-186-5p might regulate C1q/TNF-related protein 3 and Yin Yang 1 pathway to aggravate myocardial ischemia/reperfusion-induced injury after PCI, which led to the occurrence of MACE ( 27 , 28 ). (2) as mentioned above, exosomal miR-186-5p could regulate various pathways to facilitate atherosclerosis to induce MACE ( 15 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this finding, we also discovered that high level serum exosomal miR-186-5p after PCI and its decrement percentage <median (35%) decrement was related to increased MACE in AMI patients. The potential arguments would be that: (1) exosomal miR-186-5p might regulate C1q/TNF-related protein 3 and Yin Yang 1 pathway to aggravate myocardial ischemia/reperfusion-induced injury after PCI, which led to the occurrence of MACE ( 27 , 28 ). (2) as mentioned above, exosomal miR-186-5p could regulate various pathways to facilitate atherosclerosis to induce MACE ( 15 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…. Studies have revealed that HSPA8 [262], HSP90AA1 [259], MYH9 [339], SORT1 [335], ACTA2 [307], SOX2 [773], SMAD4 [774], GATA2 [775], CCND1 [776], SPI1 [777] and SMARCA4 [778] plays a key role in cardiovascular diseases. The altered expression of HSPA8 [174], MYH9 [209], FLNA (filamin A) [444], SOX2 [779], GATA2 [780], EP300 [781] and SMARCA4 [782] plays a key role in the progression of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…After exposure to HG and transfection with different segments, hRMECs were seeded onto 96-well culture plates and incubated for 4 hours with 10 μl of CCK 8 solution. The data were measured at 490 nm using a microplate reader [ 17 ].…”
Section: Methodsmentioning
confidence: 99%